Liberians say ‘no’ to hugs and handshakes to keep Ebola at bay - Franck Kuwonu; Lisa White (Africa Renewal, 2014)
At the entrances to private and public buildings in Monrovia, Liberia’s capital, a new custom has emerged since the outbreak of the Ebola virus: visitors wash their hands upon entering and exiting. Tap buckets conveniently placed in hallways dispense a mixture of water and chlorine or bleach from which people wash their hands.